2022
DOI: 10.1038/s41430-021-01056-4
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers as correlates of body composition and grip strength among adults with and without HIV: A cross-sectional study in Ethiopia

Abstract: Background: Changes in body composition and muscle strength are common among individuals with HIV. We investigated the associations of inflammation with body composition and grip strength in adults with and without HIV. Methods: Cross-sectional study among Ethiopian treatment-naïve individuals with and without HIV. Fat mass and fat-free mass adjusted for height (kg/m 2 ) were used as indicators of body composition. Results: 288/100 individuals with/without HIV were included between July 2010 and August 2012.Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Reduced muscle function in the context of this study may arise from malnutrition and/or chronic inflammation [12]. In addition, myofiber atrophy occurs in vitamin D deficiency, which is more common in HIV infection [41].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Reduced muscle function in the context of this study may arise from malnutrition and/or chronic inflammation [12]. In addition, myofiber atrophy occurs in vitamin D deficiency, which is more common in HIV infection [41].…”
Section: Discussionmentioning
confidence: 93%
“…Studies of HIV in adults report impaired muscle function [8,9]; however, few studies, particularly in Africa, have investigated muscle function in CWH. Those reported are often small, lack a control population [10,11], or focus on treatment-naive individuals [12]. A recent systematic review of just five cross-sectional studies (none in Africa), totalling 197 adolescents (age 16-18 years) living with HIV, identified reduced muscle strength and physical fitness compared with uninfected peers [13].…”
Section: Introductionmentioning
confidence: 99%